Employee Participation in Decision-Making and its Impact on Organizations - Amiri, Gholam Huassein; Mirzaie, Reza (Journal of Social Sciences - Kabul University, 2021)
In this article, employee participation in decision-making and its impact on organizations reviewed. Rational decisions play an important role in achieving the effectiveness and efficiency of organizations. Employee participation in decision-making helps organizations make rational decisions. This participation can be done in different ways considering the conditions of the organization. In this research which is a library research, first-hand scientific sources including scientific books, articles and dissertations were used to collect information. The information was analyzed by descriptive-analytical method. This study shows that organizations can involve employees in decision making in both individual and group methods, but this participation in decision-making is not always useful and the organization should consider the conditions of the organization, organizational goals, employee's level and other influential components. Scholars have also acknowledged that participation can have both positive and negative functions.